Strategi Coping Mahasiswa Tingkat Akhir Dalam Menghadapi Tekanan Penyelesaian Skripsi di Universitas Teknologi Sumbawa - Ulya Mulyati; Abbyzar Aggasi (INDO PUBLISHING, 2026)
This study aims to describe the coping strategies employed by final-year students of the Communication Studies Program at Sumbawa University of Technology in dealing with the pressures encountered during the thesis-writing process. This study employed a descriptive qualitative approach. Data were collected through in-depth interviews, observation, and documentation. The research participants were selected using purposive sampling, consisting of final-year students who were currently completing or had completed their undergraduate thesis. Data were analyzed through the stages of data reduction, data display, and conclusion drawing. The trustworthiness of the data was ensured through source triangulation and technique triangulation. The findings indicate that students experienced various forms of pressure during the thesis-writing process, including difficulties in determining a research topic, obstacles during the supervision process, time management issues, and pressure from both their surroundings and themselves. To cope with these challenges, students employed two types of coping strategies based on Lazarus and Folkman's theory (1984): Problem-Focused Coping and Emotion-Focused Coping. Problem-Focused Coping was applied by seeking practical solutions to the problems encountered, while Emotion-Focused Coping was used to regulate emotions and reduce psychological stress. The findings reveal that Emotion-Focused Coping was the most dominant strategy, as it was perceived to be more effective in helping students maintain emotional stability and reduce stress during the thesis completion process.